Tafsir Tematik Al-Qur'an tentang Hak Asasi Manusia: Analisis Konstruksi Nilai-Nilai Universal - Hasniati, Hasniati; Abubakar, Achmad; A. Muin, Muhammad Irham (Universitas Islam Negeri Alauddin Makassar, 2024)
Human rights are unique and universal rights for humans from birth. Human rights in Islam or from the perspective of the Koran mean unique human rights. This is a natural and fundamental obligation given by Allah SWT. From an Islamic perspective, human rights are related to the concept of equality. This is Q.S. Al Hujjarat verse 13. This article uses a research method with a qualitative approach and a literature review by collecting some information related to library research as a data source. Several theoretical studies deal with understanding human rights, human rights and obligations, and equality and legal status from an Islamic perspective. The conclusion of the author's article is that from an Islamic perspective, human rights are born directly from God Almighty and cannot be taken away or taken away, so they existed long before they became basic rights inherent in individuals. Therefore, values Human rights and their universal principles are part of the spirit and values of Sharia law.